Вербалізація концепту «мовчання» в «Щоденнику» Олександра Довженка - Коловоротна, Наталя; Kolovorotnaya, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто особливості вербалізації концепту «мовчання» в щоденниковому дискурсі, зокрема в записах О. Довженка. Проаналізовано амбівалентність мовчання в сприйнятті письменника, конотативне забарвлення соціального мовчання, його вираження засобами української мови.The article discusses the features of verbalization of a culturally significant concepts of «silence» in the diary discourse Dovzhenko. Diary entries scriptwriter show that silence, in particular social, he sees the negative connotation because it is, in the opinion of Dovzhenko, indicating noncompliance with civic duty silent, its weak civilian position of weakness. Positively connote acts ritual silence in remembrance of the situation, failure to comply with such silence is considered the author of the «Diary» as a spiritual degeneration, public indifference, lack of respect for the dead. Silence may indicate their ability to be a strategy and execute addressee diskontaktnuyu function. Verbalization of the concept for the «silence» A. Dovzhenko used pure number of lexical and nadslovnyh verbal means, some of them are semantically transformed.
Verbalization of the Concept of «Silence» in the «Diary» by Alexander Dovzhenko
Keywords: концепт; вербалізація; щоденниковий дискурс; конотативне забарвлення; concept; verbalization; diary discourse; connotative color